Muzeum-archiwum pamięci. Uwagi na temat roli materiałów archeologicznych w muzeach-miejscach pamięci na przykładzie KL Plaszow - Śmietana, Marta; Karski, Kamil (Folia Praehistorica Posnaniensia, 2019)
The issues of memory, heritage, and archaeology are strictly connected to the archaeology of the contemporary past and the Nazi period. That connection is a new field of research that lead to the reconceptualization of ideas of a museum, archives, and their relations to memory. In the paper authors discuss the case study of the area of former labor and concentration camp Plaszow in Krakow (1942–1945). Since 2016, numerous archeological research and education programs were conducted by the Museum of Krakow. The main purpose of documentation, surface surveys, and excavations was preservation of the architectural relicts and landscape, and supplementing the historical knowledge of authentic archaeological sources. The results of the research were related to the preparation of the boundaries for the future commemoration of the former camp’s area and its history as a museum and memorial site. The outcome of the archaeological activity is collection of artifacts, documentation and archaeological knowledge that influenced the idea of commemoration in its specific way. The article attempts to answer the questions about the categories of archives and museums.